Kajian Antropologis Dalam Perspektif Iman Kristen - Telaumbanua, Yohanes; Suhadi (Shalom: Jurnal Teologi Kristen, 2025)
Anthropological studies in the perspective of Christian faith aim to understand the nature of humans as God's creatures in relation to others and the environment based on theological principles. The background of this study departs from the debate between secular and theological views on the origin and development of humans, where the Christian anthropological approach provides an understanding that humans are created in the image and likeness of God (Imago Dei) and have unique moral and spiritual purposes. This study uses a qualitative method with a literature study approach, analyzing theological sources, the Bible, and relevant anthropological literature. The main findings of the study indicate that the concept of Imago Dei not only affirms human dignity, but also implies ethical responsibility in social and ecological relations. In addition, this study found that Christian faith provides a unique perspective on the dynamics of human culture and identity, which is different from the naturalistic approach in secular anthropology. The results of this study confirm that Christian anthropology not only contributes to understanding human existence from a faith perspective, but also provides a basis for more ethical and transformative social engagement. Thus, this study enriches the academic discourse on the relationship between faith and science, and encourages an integrative approach in understanding the complexity of human beings in a cultural and spiritual context.Abstrak: Kajian antropologis dalam perspektif iman Kristen bertujuan untuk memahami hakikat manusia sebagai makhluk ciptaan Tuhan dalam relasi dengan sesama dan lingkungan berdasarkan prinsip-prinsip teologis. Latar belakang penelitian ini berangkat dari perdebatan antara pandangan sekuler dan teologis mengenai asal-usul serta perkembangan manusia, di mana pendekatan antropologi Kristen memberikan pemahaman bahwa manusia diciptakan menurut gambar dan rupa Allah (Imago Dei) serta memiliki tujuan moral dan spiritual yang khas. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi pustaka, menganalisis sumber-sumber teologis, Alkitab, serta literatur antropologi yang relevan. Temuan utama penelitian menunjukkan bahwa konsep Imago Dei tidak hanya menegaskan martabat manusia, tetapi juga mengimplikasikan tanggung jawab etis dalam hubungan sosial dan ekologis. Selain itu, kajian ini menemukan bahwa iman Kristen memberikan perspektif unik tentang dinamika budaya dan identitas manusia, yang berbeda dari pendekatan naturalistik dalam antropologi sekuler. Hasil penelitian ini menegaskan bahwa antropologi Kristen tidak hanya berkontribusi dalam memahami keberadaan manusia dari sudut pandang iman, tetapi juga memberikan dasar bagi keterlibatan sosial yang lebih etis dan transformatif. Dengan demikian, kajian ini memperkaya diskursus akademik mengenai hubungan antara iman dan ilmu, serta mendorong pendekatan integratif dalam memahami kompleksitas manusia dalam konteks budaya dan spiritual